Analisis Isi Buku Teks Teknologi Media Pembelajaran Sebagai Sumber Belajar Mahasiswa - Fifit Fitriansyah (Cakrawala - Jurnal Humaniora, 2019)
In a textbook learning has an important role. Textbooks can also be seen as learning media, more than that textbooks can also be interpreted as the nutrient of learning, so that the existence of a textbook cannot be underestimated. Textbooks or textbooks are a significant learning tool for almost all subjects in the curriculum. Thus, in managing textbooks it is necessary to have an analysis of the contents of the book in order to see the advantages and disadvantages of this book. The method used in this research is Content Analysis which is commonly used in analyzing a text or book. The results of this study are that this book is very interesting and relevant to be used by teachers or educators in designing learning in accordance with the needs and learning objectives. Keywords: Content Analysis, Text Books, Instructional Media